In Vivo Effect of Catharanthus roseus Crude Extracts on Pathogenic Bacteria Isolated from Skin infections - A.Almakhzumi, Auhoud; H.Aldulaimy, Hind (Iraqi Journal of Science, 2023)
This study includes collection of 70 swabs samples of burns from patients wereadmitted in three hospitals (Baghdad, Al- Numaan and burns injuries Hospital). Allswabs samples were cultured on blood and MacConkey agar media to isolate andidentify pathogenic bacteria according to their morphological , biochemical andgrowth characters. Growth of bacteria on selective media showed the followingresults: Pseudomonas aeroginosa 44.28% , Klebsiella pneumonia 30% ,Staphylococcu saureus 8.57% , Escherichia coli 4.28% , Proteus vulgaris 4.28 % ,Enterobacter spp. 5.71% , Acinetobacter baumanni 2.89 %. Different concentrationswere prepared from leaves ethanolic crude extract of Catharanthus roseus , then theanti-bacterial activity of this extract was evaluated in vivo. Burns were achievedexperimentally in Albino mice and contaminated with pathogenic bacteria andevaluate the ability of extract in healing of these infected burns. Results showed thatthe extract accelerate burns healing within 7days.